Pengaruh Pendekatan Science, Technology, Engineering, and Mathematics (STEM) terhadap Keterampilan Proses Sains Siswa Sekolah Dasar - Firdaus, Muhammad Dafa; Rahayu, Puji; Nuraeni, Fitri (Pendidikan Guru Madrasah Ibtidaiyah STIT Palapa Nusantara, 2023)
Science process skills are skillssthattmust be mastereddby students in the scienceelearning process. Theelow skills offstudents' science processes are the main basissfor this research. This study aims to determine the effect and increase the application3of STEM approaches to the science2process skills of elementary school students. The type of research used in this study was quasi-experimental with a non-equivalent control group design. The sample consisted of two classes of fifth grade elementary school students, which were then divided into experimental classes that received treatment with the application of learning using a STEM approach and control classes that received learning using a scientific approach. The results of data analysis showed that learning with the STEM approach resulted in an increase of 0.81 and was in the high category, while the scientific approach resulted in an increase of 0.38 and was in the medium category. These results show that students' science process skills improved better in classes that applied a STEM approach compared to classes that applied a scientific approach. In addition, there was an influence from the STEM approach on improving the science process skills of elementary school students by 16.9%. In this study, it was concluded that: 1) The improvement of science process skills of students whoareceived learning1using a STEM approach1was better than3students who received learning1with a scientificiapproach. 2) STEM approaches to science learning affect students'iscience1processiskills.